More Harm than Good? The Moral Maze of Complementary and Alternative Medicine - Ernst, Edzard (Springer International Publishing, 2018)
This book reveals the numerous ways in which moral, ethical and legal principles are being violated by those who provide, recommend or sell 'complementary and alternative medicine' (CAM). The book analyses both academic literature and internet sources that promote CAM. Additionally the book presents a number of brief scenarios, both hypothetical and real-life, about individuals who use CAM or who fall prey to ethically dubious CAM practitioners. The events and conundrums described in these scenarios could happen to almost anyone. Professor emeritus of complementary medicine Edzard Ernst together with bioethicist Kevin Smith provide a thorough and authoritative ethical analysis of a range of CAM modalities, including acupuncture, chiropractic, herbalism, and homeopathy. This book could and should interest all medical professionals who have contact to complementary medicine and will be an invaluable reference for patients deliberating which course of treatment to adopt.